A Complex Adaptive Systems Engineering Methodology. Issue 2 (6th August 2021) - White, Brian E.; Bouyaud, Mickael
ABSTRACT: In recognizing a system's complexity reflects human complexity, this treatise suggests ways to achieve effective progress in complex systems engineering by intentionally including people as an integral system part to develop or improve. We apply essential and relevant multi‐disciplinary techniques in addition to the necessary enabling technologies. However, we focus on human aspects making or breaking the system. Although this methodology can apply to almost any endeavor, software engineering is our specific example domain area.